Transfer behaviours and influences of high-order hot judder in passenger cars. (February 2018) - Xu, Xinfu; Winner, Hermann
Hot judder consists of brake-induced forced vibrations which are characterized by hot spots on the brake discs. It mainly influences the driving comfort as perceived by the driver as vibrations and low-frequency noises. This article concentrates on the transfer behaviours of high-order hot judder and its effects on the driver's subjective perception. A novel testing method is applied in this investigation, simulating the high-order hot judder by using discs that are artificially modified to generate tenth-order disc thickness variations or tenth-order lateral run-out. A high quality is achieved with respect to identification of the transfer functions from the brake pressure variation and the brake torque variation to the essential driver interface quantities of hot judder. The threshold values of the brake pressure variation and the brake torque variation for perception of the high-order hot judder in a high-frequency range are obtained on the basis of a regression analysis between subjective evluaitons and objective evaluations of the hot-judder-induced vibrations and the selected critical sound pressure level inside a vehicle. Generally, a brake pressure variation of more than 10 bar or a brake torque variation of 100 Nm is required for perception of the high-order judder-induced vibrations, whereas a brake torque variation of 50 Nm can result in annoying noises. According to the transfer functions and the threshold values of the brake pressure variation and the brake torque variation, the drone noise is shown to be the main reason for potential customer complaints arising from high-order hot judder. The practical significance of high-order judder to the driver's perception is suitably quantified for the first time. Also, with these results, the impacts of high-order hot judder can be assessed from the observed brake pressure variation and the observed brake torque variation, which are mainly measured using dynamometers.